Upon Opening the Black Box and Finding It Full: Exploring the Ethics in Design Practices. (May 2015) - Steen, Marc
Contemporary design practices, such as participatory design (PD), human-centered design (HCD), and codesign, have inherent ethical qualities, which often remain implicit and unexamined. Three design projects in the high-tech industry were studied using three ethical traditions as lenses. Virtue ethics helped to understand cooperation, curiosity, creativity, and empowerment as virtues that people in PD need to cultivate, so that they can engage, for example, in mutual learning and collaborative prototyping. Ethics of alterity (Levinas and Derrida) helped to understand human-centered design as a fragile encounter between project team members and prospective users, and foregrounds the ethics in these encounters: our tendencies to "grasp the other" and to "program invention." And pragmatist ethics (Dewey) helped to understand codesign as a process of joint inquiry and imagination, involving the organization of iterative processes of problem setting and solution finding, with moral qualities. When we open the "black boxes" of design practices, we find them filled with ethics. Moreover, it is proposed that design practitioners need to make explicit their practices' inherent ethical qualities and that they can do that by embracing reflexivity.